Effects of morphology in the nativization of loanwords: The borrowing of /s/ in Xitsonga - Lee, Seunghun J; Hlungwani, Crous M (Stellenbosch Papers in Linguistics Plus, 2020)
This paper argues that the nativization of loanwords can result from pressure from morphology based on patterns of English loanword adaptations in Xitsonga, a southern Bantu language. The /s/ in /sC/ clusters of English is always realized in Xitsonga borrowings as [s] in non-initial positions, but the /s/ is realized with variations when it appears in the initial position: faithfully with an alveolar fricative [s], or with a palatal fricative [ʃ]. A loanword adaptation experiment confirms that this position-sensitive variation is part of the grammatical knowledge of Xitsonga speakers. The adaptation of initial /sC/ clusters to [ʃiC] in the nativization process is argued to result from pressures to incorporate loanwords into the existing noun class system: a case where morphology triggers phonological changes. What is also important is the non-occurrence of palatalization in non-initial positions. Since non-initial consonants are not subject to the same morphological pressure, the nativatization process of /sC/ to [ʃiC] is blocked.